Evaluasi Pengembangan Kawasan Strategis Pariwisata Daerah Banten Lama Kota Serang - Amrulloh, Amim; Jumiati, Ipah Ema; Stiawati, Titi (Faculty of Social Science, Universitas Negeri Padang, 2024)
This research focuses on the Evaluation of the Development of the Banten Lama Regional Tourism Strategic Area, Serang City, Banten Province. with the aim of knowing the results of the evaluation of the Old Banten Development. According to (Dunn 2003), there are six indicators for evaluation, namely adequacy, equity, responsiveness and suitability and this research uses descriptive qualitative research methods. Informants in the research came from elements of the Serang city government, Banten province and the center as well as other stakeholders. The results of the research are known. The effectiveness of the development of the Banten Sultanate area is still less than optimal, as indicated by the division of tasks and functions that are not yet synergistic, there are unfinished buildings, minimal parking management, weak implementation of sanctions related to acts of vandalism, minimal care and maintenance, minimal provision of signs, there is resistance. development by residents. Efficiency is still weak due to the minimal development budget for the Sultanate of Banten. Adequacy is still minimal, indicated by the absence of a special decree to manage Banten Lama, the lack of parking attendants, the lack of trash cans, seating, grass cleaning equipment, and the absence of communication equipment in the field. Leveling is still less than optimal, which is indicated by the lack of discipline among visitors and the public regarding cleanliness, while the advantage is that the community gets economic income. Good responsiveness is characterized by officers who are fast and alert. Less than optimal accuracy is indicated by the lack of comprehensive physical development.